Pharmacogenomics and active surveillance for serious adverse drug reactions in children. (September 2010) - Loo, Tenneille T; Ross, Colin JD; Sistonen, Johanna; Visscher, Henk; Madadi, Parvaz; Koren, Gideon; Hayden, Michael R; Carleton, Bruce C
Juxtaposing clinical pharmacology with human genetics, pharmacogenomics utilizes a patient's genetic information to identify genetic variants that have the potential to provide clinically relevant predictions of toxicity and efficacy. The goal is to develop personalized and genetic-based predictions of an individual's drug response and likelihood of experiencing an adverse drug reaction. The Canadian Pharmacogenomics Network for Drug Safety (CPNDS) has implemented active adverse drug reaction surveillance to monitor and discover genetic markers related to serious adverse drug reactions in the pediatric population. Evidence-based pharmacogenomics research will inform public policy and influence drug benefit–risk decision-making. Regulatory processes and future challenges in pharmacogenomics research will be discussed.